DAN BROWN'S ANGELS AND DEMONS: A NARRATIVE OR PROCEDURE TEXT? - Subur Wardoyo (Soegijapranata Catholic University, 2010)
This essay attempts to discuss the fallacies of a genre based classification of texts. It will stress the point that genres are not fixed and pre-given forms by thinking of texts as performances of genre rather than reproductions of a class to which they belong, and by following Austin perlocutionary act in stressing the fact that the writer's intended locutionary act might not be the same with the reader'sperlocutionary act. If, after reading this essay, the reader is willing not to takefor granted that such a text as Angels and Demons can be nothing else but a narrative, it will have served itspurpose.